A mediação de leitura literária na biblioteca: saberes, práticas e competência do(a) bibliotecário(a)-educador(a) - Tavares, Ane Carolina Randig (2023)
The aim of this study is to reflect on the social role of the librarian in the promotion and dissemination of literary reading for children and adolescents in school libraries. The School Library is a political issue, so instituting reading and library policies is critical to democratizing access to various sources of information, promoting the reading of literary books and contributing to the formation of competent readers through a continuous process of learning. Embedding the school library in the teaching process offers students the opportunity to expand their knowledge, through the various resources and materials available in this educational environment. Given the possibilities of this space and the scarcity of research in librarian-led literary reading mediation, this investigation discusses the practices of reading mediation that occur in community school libraries, entitled “Schools of the Future” linked to the municipal schools of São Carlos-SP. From the interviews conducted with librarians, we seek to understand the knowledge, practices and dimensions of competence involving these activities to answer the central question: how does literary reading mediation relate to the dimensions (technical, aesthetic, ethics, politics) of the librarian’s professional competence? This qualitative research project uses oral history, since it analyzes subjective elements of the interviewed librarians. The theoretical foundation is very diverse, and its main authors are: Bakhtin (1981, 1997), Candido (2011), Castrillón (2011), Chartier (1999; 2003; 2004), Colomer (2007), Cosson (2014; 2018), Freire (1987; 2011) , Kleiman (1995; 2005), Lajolo (2016), Petit (2008; 2013; 2017), Reyes (2010; 2012) that address reading and literature; Bicheri and Almeida Júnior (2013), Bortolin (2010), Campello (2003; 2015), Campello et al. (2012), Milanesi (2002) that discuss the school library and the librarian; Abad (2003), Bretas (2014) that discuss public policies related to library and reading; Vitorino (2020), Rios (2010) that present the dimensions of professional competence. We concluded that: 1) the librarian is a mediator-educator and is fully aware of his social and educational function by committing to the work of literary reading mediation; 2) The competence that involves their knowledge is multifaceted; 3) Sensitivity and empathy are necessary to nurture a pleasant, critical and significant reading experience; 4) Competence encompasses the notion of doing one's duty well and requires a set of knowledge and skills that imply a position in relation to the context in which one is inserted (ethical and political dimensions); 5) Although libraries have some limitations, these spaces have contributed to the formation of literary readers; 6) The need for investments in infrastructure of the municipal school libraries is urgent so that this important project continues to be strengthened; 7) There is a need to elaborate municipal public policy for the acquisition of books and renewal of collections as well as to ensure that external activities can happen in the library (i.e., hiring storytellers and writers), ensuring the effective functioning of these spaces that enrich the reading formation of library patrons.